PENGARUH STRATEGI TEAM QUIZ TERHADAP HASIL BELAJAR IPS KELAS V SDN SEMBUNGHARJO 02 SEMARANG - Istikhomah, Nirwana Nurul; Subekti, Ervina Eka; Wardana, Muhammad Yusuf Setia (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
The goal to be achieved in this study is to determine differences in student learning outcomes between classes using the Quiz Team strategy and classes using conventional strategies. The research method uses experiments with Quasi Experimental Design pretest and posttest designs in the experimental class and the control class. The samples taken were VA class students with a total of 25 students and VB class with a total of 25 students. Data collection techniques are tests, observations, interviews and documentation. The analysis technique uses the t test of learning outcomes in the experimental class and control class with a level of 0.05, it is proven that the results of the hypothesis are tcount ttable, namely 3.305 2.010, so Ha is accepted, meaning that there is a difference in the average class using the Quiz Team strategy with classes using conventional strategies. Based on the results of the study that the Quiz Team learning strategy can be used as an alternative in social studies learning